Negative electrode active material, preparation and application thereof, sodium ion battery negative electrode material, sodium ion battery negative electrode and application

The negative electrode active material is prepared by combining petroleum-based materials and hard carbon precursors, which solves the problem of low carbon production rate of hard carbon material precursors, improves the performance and efficiency of the negative electrode of sodium ion battery, and reduces costs.

CN119569022AActive Publication Date: 2025-03-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311149382.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

The precursors of existing hard carbon materials have low carbon yield, high cost and poor performance, which limits their application in sodium ion batteries.

Method used

The negative electrode active material is prepared by combining petroleum-based materials and hard carbon precursors. Through pretreatment and high-temperature carbonization, the carbon production rate is improved and the cost is reduced.

Benefits of technology

The reversible capacity and first-week Coulomb efficiency of the sodium ion battery negative electrode are improved, the material cost is reduced, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569022A_ABST
    Figure CN119569022A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, and discloses a negative electrode active material and preparation and application thereof, a sodium-ion battery negative electrode material, a sodium-ion battery negative electrode and application, and the method comprises the following steps: (1) mixing a petroleum-based material and a hard carbon precursor with a solvent to obtain mixed slurry; (2) drying the mixed slurry obtained in the step (1); (3) performing pretreatment and high-temperature carbonization on the product in the step (2) to obtain a negative active material; wherein the mass ratio of the petroleum-based material to the hard carbon precursor in the step (1) is (0.1-4): 1. The preparation method of the negative electrode active material adopts a mode of compounding a petroleum-based material and a hard carbon precursor, and is simple and easy for industrial amplification; meanwhile, the common advantages of the two materials are achieved, the overall carbon production rate is increased, and the reversible capacity and the first-week coulombic efficiency of the negative electrode of the sodium-ion battery can be jointly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a negative electrode active material and its preparation and application, as well as a sodium ion battery negative electrode material and a sodium ion battery negative electrode and its application. Background Art

[0002] Secondary batteries are an important medium for converting clean energy such as solar energy, wind energy, and tidal energy into chemical energy. They can effectively solve the regional and intermittent limitations of clean energy and achieve stable storage and continuous output of energy. Existing secondary battery systems, such as lithium-ion batteries, have the advantages of high energy density, good cycle stability, and low self-discharge. They have been widely used in mobile electronics, communication equipment, electric devices, and electric vehicles. However, they are limited by the shortage of lithium resources in large-scale energy storage. The development of new high-energy-density secondary batteries to cope with resource shortages is a research focus in this field. The application of sodium-ion batteries can not only alleviate the global lithium resource shortage and narrow the gap between supply and demand; on the other hand, the abundant sodium salt reserves and mature extraction processes jointly determine the lower material cost and cost fluctuation range of sodium-ion batteries.

[0003] Similar to the working principle of lithium-ion batteries, the design and development of electrode materials that can accommodate the stable insertion and extraction of sodium ions is the key to the commercialization of sodium-ion batteries. In academia, a variety of sodium-ion battery negative electrode materials have been developed, including conversion reaction materials, alloying materials, titanium-based materials and carbon-based materials. Amorphous carbon-based negative electrodes (including hard carbon and soft carbon) show high reversible specific capacity and good cycle performance in sodium-ion batteries. Since their discovery, researchers have conducted a lot of exploration and research on this type of material. Hard carbon materials are currently the most promising negative electrode materials for sodium-ion secondary batteries, but the current carbon yield of precursors for producing hard carbon is low, resulting in high costs for hard carbon materials, which restricts their commercial application. The preparation of carbon-based negative electrode materials with petroleum-based products has a high carbon yield, low cost, and a complete raw material supply chain, which is easy to quickly integrate into the market. However, the direct high-temperature carbonization of materials such as petroleum coke and asphalt produces soft carbon materials, which have problems such as low specific capacity and high sodium storage voltage. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low carbon yield, high cost and poor performance of hard carbon material precursors in the prior art, and to provide a negative electrode active material and its preparation and application, as well as a sodium ion battery negative electrode material and a sodium ion battery negative electrode and application. The preparation method of the negative electrode active material adopts a composite method of petroleum-based materials and hard carbon precursors. The preparation method is simple and easy to industrially scale up; at the same time, it has the common advantages of the two materials, improves the overall carbon yield, and can achieve a common improvement in the reversible capacity and the first-week coulomb efficiency of the sodium ion battery negative electrode.

[0005] In order to achieve the above object, the present invention provides a method for preparing a negative electrode active material in a first aspect, wherein the method comprises the following steps:

[0006] (1) mixing a petroleum-based material and a hard carbon precursor with a solvent to obtain a mixed slurry;

[0007] (2) drying the mixed slurry obtained in step (1);

[0008] (3) The product of step (2) is pretreated and carbonized at high temperature to obtain a negative electrode active material;

[0009] Wherein, the mass ratio of the petroleum-based material to the hard carbon precursor in step (1) is 0.1-4:1.

[0010] Preferably, the softening point of the petroleum-based material is 100-300°C, preferably 200-300°C.

[0011] Preferably, the mass percentage of ash in the petroleum-based material is 0-0.5wt%, preferably 0-0.1wt%.

[0012] Preferably, the pretreatment conditions include: pretreatment temperature of 160-350°C, preferably 180-250°C, heating rate of 1-6°C / min, preferably 2-5°C / min, pretreatment time of 2-60 hours, preferably 24-60 hours.

[0013] The second aspect of the present invention provides a negative electrode active material prepared by the preparation method described in the first aspect.

[0014] The third aspect of the present invention provides an application of the negative electrode active material described in the second aspect in a sodium ion battery.

[0015] The fourth aspect of the present invention provides a negative electrode material for a sodium ion battery, wherein the negative electrode material contains a negative electrode active material and a binder, wherein the negative electrode active material is the negative electrode active material described in the second aspect.

[0016] A fifth aspect of the present invention provides a sodium ion battery negative electrode, the negative electrode comprising a current collector and a negative electrode material coated and / or filled on the current collector, the negative electrode material being the negative electrode material described in the fourth aspect of the present invention.

[0017] The sixth aspect of the present invention provides the use of the sodium ion battery negative electrode described in the fifth aspect in a sodium ion battery.

[0018] Through the above technical solution, the beneficial effects obtained are as follows:

[0019] (1) In the present invention, the negative electrode active material is prepared by using petroleum-based materials and hard carbon precursors as carbon sources, and the negative electrode active material is obtained after pretreatment and high-temperature carbonization. The preparation method is simple and easy to scale up industrially. It has the advantages of both soft carbon and hard carbon materials, improves the overall carbon yield, and reduces the cost;

[0020] (2) In the present invention, preferably, the prepared negative electrode active material is used to prepare a negative electrode material for a sodium ion battery, which is used in a sodium ion battery and has a high reversible capacity and first-cycle coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the XRD spectrum of the negative electrode active material prepared in Example 1;

[0022] Figure 2 This is a SEM image of the negative electrode active material prepared in Example 1. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] A first aspect of the present invention provides a method for preparing a negative electrode active material, wherein the method comprises the following steps:

[0025] (1) mixing a petroleum-based material and a hard carbon precursor with a solvent to obtain a mixed slurry;

[0026] (2) drying the mixed slurry obtained in step (1);

[0027] (3) The product of step (2) is pretreated and carbonized at high temperature to obtain a negative electrode active material;

[0028] Wherein, the mass ratio of the petroleum-based material to the hard carbon precursor in step (1) is 0.1-4:1.

[0029] In the present invention, petroleum-based materials and hard carbon precursors are mixed as carbon sources. The petroleum-based materials have a high carbon yield, and the addition of hard carbon precursors can obtain soft and hard carbon composite negative electrode active materials after high-temperature carbonization treatment, thereby increasing the specific capacity of the material and reducing the sodium storage voltage.

[0030] According to the present invention, preferably, the mass ratio of the petroleum-based material and the hard carbon precursor in step (1) is 0.1-4:1, such as 0.1:1, 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1.2:1, 1.6:1, 2:1, 2.4:1, 2.8:1, 3.2:1, 3.6:1, 4:1, or any range between the two, preferably 0.4-2.4:1. The mixing of the petroleum-based material and the hard carbon precursor in the above mass ratio can not only combine the advantages of the two precursors, but also the hard carbon precursor can induce an increase in disorder in the soft carbon structure during the pyrolysis process. The negative electrode material obtained by further preparing the negative electrode active substance is used for sodium ion batteries and has high reversible capacity and first-cycle coulombic efficiency.

[0031] According to the present invention, the petroleum-based material in step (1) is a conventional carbon material obtained from petroleum as a raw material in the art, preferably at least one selected from asphalt, petroleum coke and needle coke, more preferably asphalt. In the present invention, the source of the petroleum-based material is not particularly limited, and can be commercially available or prepared by existing methods, and is a powder with uniform particle size distribution.

[0032] According to the present invention, preferably, the softening point of the asphalt is 100-300° C., preferably 200-300° C. In the present invention, the test method for the softening point of the asphalt is to place the asphalt raw material in a special test tube, heat it at a stable heating rate under a nitrogen atmosphere, and continuously pierce the asphalt with a steel needle rod with a diameter of 1 mm during the process. When the asphalt becomes soft and begins to stick to the steel needle, the temperature at this time is recorded, which is the softening point of the asphalt.

[0033] According to the present invention, preferably, the mass percentage of ash in the petroleum-based material is 0-0.5wt%, preferably 0-0.1wt%. In the present invention, ash has the conventional interpretation in the art, and refers to the inorganic matter remaining after the petroleum-based material is burned or calcined. In the present invention, the mass percentage of ash in the petroleum-based material is measured by a roasting method: (1) Record the initial mass of the petroleum-based material sample; (2) Put the petroleum-based material sample into a drying oven and dry it to constant weight at a constant temperature of 110℃-115℃; (3) Take out the sample, put it into a roaster, first bake it at a low temperature for 30 minutes, and then raise it to 815℃ and bake it to constant weight; (4) Take out the sample, put it into an air cooler to cool, weigh the sample, and the mass difference is the ash content, and the ratio of the ash content to the mass of the petroleum-based material sample is recorded as the mass percentage of ash.

[0034] In the present invention, the above petroleum-based material is mixed with a hard carbon precursor. The petroleum-based material has a high softening point and a low ash content, which is beneficial to improving the carbon yield and the selection of the pretreatment process.

[0035] According to the present invention, preferably, the hard carbon precursor is starch and / or lignin, preferably starch. In the present invention, the type of starch is not particularly limited, and those skilled in the art can choose conventional starch, which can be natural starch and / or processed starch, and the natural starch includes but is not limited to at least one of bean starch, potato starch, wheat starch, sweet potato starch, cassava starch, rice starch, corn starch, sweet potato powder and kudzu powder. The processed starch includes but is not limited to at least one of pregelatinized starch, oxidized starch, cross-linked starch, esterified starch and deformed starch.

[0036] In the present invention, the source of the hard carbon precursor is not particularly limited, and can be purchased commercially or prepared by existing methods, and those skilled in the art can make an adaptive selection.

[0037] According to the present invention, there is no particular limitation on the type of the solvent, and those skilled in the art can select conventional volatile organic solvents and / or inorganic solvents in the art, as long as the petroleum-based material and the hard carbon precursor can be mixed and evaporated and removed. Preferably, the solvent is ethanol and / or water. The above solvent is added to prepare a mixed slurry, and in the subsequent sand milling process, the petroleum-based material and the hard carbon precursor can be evenly mixed, and it is environmentally friendly.

[0038] According to the present invention, there is no particular limitation on the amount of the solvent used. Preferably, the total mass ratio of the solvent to the petroleum-based material and the hard carbon precursor is 2-30:1, such as 2:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, or any range therebetween, preferably 5-15:1.

[0039] According to the present invention, preferably, step (1) further comprises sand grinding the mixed slurry, and the sand grinding conditions include:

[0040] The sand milling time is 1-10 hours, preferably 3-8 hours; the sand milling speed is 1600-2400 r / min, preferably 1800-2200 r / min. In the present invention, the sand milling equipment is not particularly limited, as long as it can sand mill the mixed slurry evenly, and those skilled in the art can select conventional sand milling equipment.

[0041] According to the present invention, preferably, in step (2), the drying treatment conditions include: spray drying under a protective atmosphere, the spray pressure is 0.1-0.4MPa, preferably 0.2-0.3MPa, and the temperature is 100-220°C, preferably 150-200°C. In the present invention, preferably, spray drying is used to treat the mixed slurry under the above conditions, so that the morphology of the mixed material can be ensured while the solvent is volatilized, agglomeration is not easily formed, the dispersion is good, and the cycle stability of the obtained negative electrode material is ensured.

[0042] In the present invention, the type of the protective atmosphere is not particularly limited, and those skilled in the art may select a conventional protective atmosphere with stable properties, preferably at least one selected from nitrogen, helium, argon and neon.

[0043] According to the present invention, preferably, the pretreatment conditions include: pretreatment temperature of 160-350°C, preferably 180-250°C, heating rate of 1-6°C / min, preferably 2-5°C / min, pretreatment time of 2-60 hours, preferably 24-60 hours.

[0044] In the present invention, preferably, the pretreatment is carried out under the above conditions, so as to maintain the initial spherical structure of the starch granules, prevent expansion and melting, and form a stable cross-linked structure.

[0045] According to the present invention, preferably, the conditions for high temperature carbonization include: reaction temperature of 1000-1300°C, preferably 1100-1300°C, heating rate of 2-10°C / min, preferably 3-8°C / min, reaction time of 0.5-4 hours, preferably 1-3 hours.

[0046] In the present invention, the equipment used for the pretreatment and high-temperature carbonization is not particularly limited, and those skilled in the art can select it adaptively. According to a specific embodiment of the present invention, the pretreatment and high-temperature carbonization are carried out in a tubular furnace.

[0047] The second aspect of the present invention provides a negative electrode active material prepared by the preparation method described in the first aspect.

[0048] According to the present invention, preferably, the interlayer spacing of the negative electrode active material is 0.36-0.4 nm, preferably 0.39-0.4 nm. This preferred embodiment is more conducive to improving the sodium storage capacity of the negative electrode active material. The interlayer spacing is the carbon interlayer spacing of the negative electrode active material, which is calculated by the Bragg equation.

[0049] Specifically, in the present invention, the XRD diffractometer used for the X-ray diffraction spectrum of the negative electrode active material is an XRD-6000 X-ray powder diffractometer (Shimadzu, Japan), and the XRD test conditions are: Cu target, Kα ray (wavelength λ = 0.154nm), tube voltage of 40kV, tube current of 200mA, and scanning speed of 10° (2θ) / min. Reference Figure 1 The X-ray diffraction spectrum of the negative electrode active material has a diffraction peak at a 2θ angle of 22.3±0.5°, which corresponds to the (002) diffraction peak of the hard carbon material, proving that the hard carbon material is generated in the negative electrode active material.

[0050] The third aspect of the present invention provides an application of the negative electrode active material described in the second aspect in a sodium ion battery.

[0051] The fourth aspect of the present invention provides a negative electrode material for a sodium ion battery, the negative electrode material comprising a negative electrode active material and a binder, wherein the negative electrode active material is the negative electrode active material described in the second aspect.

[0052] In the present invention, the negative electrode material prepared by using the negative electrode active material is used in a sodium ion battery and has high reversible capacity and first-cycle coulombic efficiency.

[0053] In the present invention, the amount and type of the binder for the electrode material can be selected in a wide range and can be selected according to conventional technical means in the art. According to a preferred embodiment of the present invention, the binder is sodium alginate, which can be provided in the form of an aqueous solution thereof. The amount of the binder can be such that the negative electrode active material is prepared into a negative electrode material through the binder, and those skilled in the art can adjust it adaptively.

[0054] A fifth aspect of the present invention provides a sodium ion battery negative electrode, the negative electrode comprising a current collector and a negative electrode material coated and / or filled on the current collector, the negative electrode material being the negative electrode material described in the fourth aspect of the present invention.

[0055] The sixth aspect of the present invention provides the use of the sodium ion battery negative electrode described in the fifth aspect in a sodium ion battery.

[0056] According to the present invention, preferably, the sodium ion battery comprises an electrode group and a non-aqueous electrolyte, wherein the electrode group and the non-aqueous electrolyte are sealed in a battery casing, the electrode group comprises a positive electrode, a negative electrode and a diaphragm, the diaphragm is located between the positive electrode and the negative electrode, and the negative electrode is the negative electrode of the sodium ion battery described in the fifth aspect.

[0057] In the present invention, the non-aqueous electrolyte refers to an electrolyte solution whose solvent is not water. Those skilled in the art can select a suitable non-aqueous electrolyte according to the composition of the sodium ion battery, and no limitation is made here.

[0058] According to a particularly preferred embodiment of the present invention, a method for preparing a negative electrode active material comprises the following steps:

[0059] (1) mixing a petroleum-based material and a hard carbon precursor with a solvent to obtain a mixed slurry;

[0060] (2) spray drying the mixed slurry obtained in step (1);

[0061] (3) The product of step (2) is pretreated and carbonized at high temperature to obtain a negative electrode active material;

[0062] Wherein, the mass ratio of the petroleum-based material to the hard carbon precursor in step (1) is 0.4-2.4:1;

[0063] In step (1), the petroleum-based material is asphalt; the hard carbon precursor is starch;

[0064] The softening point of the asphalt is 200-300°C;

[0065] The mass percentage of ash in the asphalt is 0-0.1wt%;

[0066] The interlayer distance of the negative electrode active material is 0.39-0.4 nm.

[0067] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, the room temperature is 25°C; unless otherwise specified, all reagents used are commercially available;

[0068] The microstructure of the negative electrode active materials was observed by scanning electron microscopy.

[0069] Example 1

[0070] (1) asphalt (high-temperature petroleum asphalt) and starch (corn starch) were mixed in a mass ratio of 1:1, dissolved in an ethanol solvent, wherein the mass ratio of the ethanol solvent to the asphalt and the starch was 10:1, and sand-milled for 6 hours at a sand-milling speed of 2200 r / min to obtain a mixed slurry, wherein the softening point of the asphalt was 278° C. and the ash content was 0.05 wt %;

[0071] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 180° C.;

[0072] (3) The product obtained in step (2) is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is first increased to 220° C. at a heating rate of 2° C. / min and kept at this temperature for 48 hours, and then the temperature is increased to 1200° C. at a heating rate of 5° C. / min and kept at this temperature for 2 hours, and the negative electrode active material is obtained after natural cooling.

[0073] Figure 1 To obtain the X-ray diffraction (XRD) spectrum of the negative electrode active material, Figure 1 It can be seen that there is a diffraction peak at a 2θ angle of 22.3°, which corresponds to the (002) diffraction peak of the hard carbon material.

[0074] Figure 2 To obtain the SEM image of the negative electrode active material, Figure 2 As shown, the overall structure of the material is spherical.

[0075] Example 2

[0076] (1) Asphalt (high-temperature petroleum asphalt) and starch (corn starch) were mixed in a ratio of 7:3, dissolved in an appropriate amount of ethanol solvent, and sand-milled for 8 hours at a sand-milling speed of 1800 r / min, wherein the softening point of the asphalt was 278° C. and the ash content was 0.05 wt %;

[0077] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 150° C.;

[0078] (3) placing the product obtained in step (2) in a tubular furnace, first heating the temperature to 250° C. at a heating rate of 5° C. / min and keeping the temperature for 60 hours under a nitrogen atmosphere, then heating the temperature to 1300° C. at a heating rate of 8° C. / min and keeping the temperature for 1 hour, and then cooling the temperature naturally to obtain a negative electrode active material for a sodium ion battery.

[0079] Example 3

[0080] (1) Asphalt (high-temperature petroleum asphalt) and starch (corn starch) were mixed in a ratio of 3:7, dissolved in an appropriate amount of ethanol solvent, and sand-milled for 3 hours at a sand-milling speed of 2500 r / min, wherein the softening point of the asphalt was 278° C. and the ash content was 0.05 wt %;

[0081] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 200° C.;

[0082] (3) placing the product obtained in step (2) in a tubular furnace, first heating the temperature to 180° C. at a heating rate of 2° C. / min and keeping the temperature for 24 hours under a nitrogen atmosphere, then heating the temperature to 1100° C. at a heating rate of 3° C. / min and keeping the temperature for 3 hours, and then cooling the temperature naturally to obtain a negative electrode active material for a sodium ion battery.

[0083] Example 4

[0084] (1) Needle coke (source: Sinopec Maoming Petrochemical Co., Ltd.) and starch (corn starch) were mixed in a ratio of 1:1, dissolved in an appropriate amount of ethanol solvent, and sand-milled for 6 hours at a sand-milling speed of 2200 r / min, wherein the ash content was 0.5 wt%;

[0085] (2) spray drying the mixed slurry obtained in step (1) under a nitrogen atmosphere at a spray pressure of 0.2 MPa and a temperature of 180° C.;

[0086] (3) placing the product obtained in step (2) in a tubular furnace, first heating the temperature to 220° C. at a heating rate of 2° C. / min and keeping the temperature for 48 hours under a nitrogen atmosphere, then heating the temperature to 1200° C. at a heating rate of 5° C. / min and keeping the temperature for 2 hours, and then cooling the temperature naturally to obtain a negative electrode active material for a sodium ion battery.

[0087] Example 5

[0088] The method of Example 1 is followed, except that the starch is replaced with lignin (de-alkali lignin) of equal mass, and other conditions are the same as those of Example 1, to obtain a negative electrode active material.

[0089] Example 6

[0090] The method of Example 1 is followed, except that the amount of asphalt added in step (1) is changed so that the mass ratio of asphalt to starch is 4:1. Other conditions are the same as those of Example 1, to obtain a negative electrode active material.

[0091] Example 7

[0092] The method of Example 1 is followed, except that step (2) uses forced air drying at a temperature of 110° C. to obtain a negative electrode active material.

[0093] Comparative Example 1

[0094] (1) The method of Example 1 was followed, except that asphalt and starch were mixed in a ratio of 1:1 and ball milled for 6 hours;

[0095] (2) The product obtained in step (1) is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is first increased to 220° C. at a heating rate of 2° C. / min and kept at this temperature for 48 hours, and then the temperature is increased to 1200° C. at a heating rate of 5° C. / min and kept at this temperature for 2 hours, and the negative electrode active material is obtained after natural cooling.

[0096] Comparative Example 2

[0097] (1) The method of Example 1 was followed, except that asphalt and starch were mixed in a ratio of 1:1 and ball milled for 6 hours;

[0098] (2) placing the product obtained in step (1) in a tubular furnace, heating it to 1200° C. at a heating rate of 5° C. / min under a nitrogen atmosphere and keeping the temperature for 2 hours, and then cooling it naturally to obtain a negative electrode active material for a sodium ion battery.

[0099] Test Case

[0100] The negative electrode active materials prepared in the examples and comparative examples were prepared into negative electrode plates for sodium ion batteries and assembled into batteries.

[0101] 1) Preparation of negative electrode sheet:

[0102] The negative electrode active materials obtained in the above embodiments and comparative examples after drying were mixed with an aqueous solution of sodium alginate (binder, the mass fraction of sodium alginate was 2%) at a mass ratio of 9:1, and stirred on a magnetic stirrer for 6 hours to obtain a paste slurry; the obtained paste slurry was evenly coated on the current collector copper foil, and then dried in a vacuum drying oven at 100°C for 20 hours for use.

[0103] 2) Battery assembly:

[0104] The dried negative electrode was made into a circular electrode with a diameter of 12 mm; and maintained at a pressure of 8 MPa for 30-180 seconds to obtain the negative electrode of the sodium ion battery. The metal sodium sheet was used as the counter electrode, the glass fiber was used as the diaphragm, 1 mol / L sodium hexafluorophosphate was selected as the electrolyte, and the solvent volume ratio EC (ethylene carbonate): DEC (diethyl carbonate) = 1:1 was assembled into a CR2032 button cell. The entire battery assembly was completed in a glove box to prepare a sodium ion battery.

[0105] Routine battery performance test: The battery was charged and discharged using the LAND CT2001A charge and discharge instrument from Wuhan Rambo Electronics Co., Ltd. The charge and discharge voltage range was 0V to 2.5V, and the specific capacity of the assembled sodium-ion battery was tested at a rate of 0.1C.

[0106] The performance test results of the sodium ion batteries prepared in the examples and comparative examples are shown in Table 1.

[0107] Table 1

[0108]

[0109] It can be seen from the results in Table 1 that the present invention is based on low-cost petroleum-based materials and precursor carbon sources, and prepares negative electrode active materials through low-temperature pretreatment and high-temperature carbonization, and uses them as negative electrode active materials for sodium ion batteries in sodium ion batteries, which have high reversible capacity and first-cycle coulombic efficiency.

[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode active material, characterized in that: The method comprises the following steps: (1) mixing a petroleum-based material and a hard carbon precursor with a solvent to obtain a mixed slurry; (2) drying the mixed slurry obtained in step (1); (3) The product of step (2) is pretreated and carbonized at high temperature to obtain a negative electrode active material; Wherein, the mass ratio of the petroleum-based material to the hard carbon precursor in step (1) is 0.1-4:

1.

2. The preparation method according to claim 1, wherein The mass ratio of the petroleum-based material to the hard carbon precursor in step (1) is 0.4-2.4:1; Preferably, the petroleum-based material in step (1) is selected from at least one of asphalt, petroleum coke and needle coke, preferably asphalt; Preferably, the softening point of the asphalt is 100-300°C, preferably 200-300°C; Preferably, the mass percentage of ash in the petroleum-based material is 0-0.5wt%, preferably 0-0.1wt%.

3. The preparation method according to claim 1 or 2, wherein The hard carbon precursor is starch and / or lignin, preferably starch; Preferably, the solvent is ethanol and / or water; Preferably, the total mass ratio of the solvent to the petroleum-based material and the hard carbon precursor is 2-30:1, preferably 5-15:

1.

4. The preparation method according to any one of claims 1 to 3, wherein The pretreatment conditions include: pretreatment temperature of 160-350°C, preferably 180-250°C, heating rate of 1-6°C / min, preferably 2-5°C / min, pretreatment time of 2-60 hours, preferably 24-60 hours; Preferably, the conditions for high temperature carbonization include: reaction temperature of 1000-1300°C, preferably 1100-1300°C, heating rate of 2-10°C / min, preferably 3-8°C / min, reaction time of 0.5-4 hours, preferably 1-3 hours; Preferably, the pretreatment and high-temperature carbonization are carried out under a protective atmosphere, and the protective atmosphere is selected from at least one of nitrogen, helium, argon and neon.

5. The preparation method according to any one of claims 1 to 4, wherein: Step (1) further comprises sand grinding the mixed slurry, wherein the sand grinding conditions include: The sanding time is 1-10 hours, preferably 3-8 hours; the sanding speed is 1600-2400 r / min, preferably 1800-2200 r / min; Preferably, in step (2), the drying treatment conditions include: spray drying under a protective atmosphere, a spray pressure of 0.1-0.4 MPa, preferably 0.2-0.3 MPa, and a temperature of 100-220°C, preferably 150-200°C.

6. The negative electrode active material obtained by the preparation method according to any one of claims 1 to 5; Preferably, the interlayer distance of the negative electrode active material is 0.36-0.4 nm, preferably 0.39-0.4 nm.

7. Use of the negative electrode active material according to claim 6 in a sodium ion battery; Preferably, the negative electrode active material is used in a negative electrode material for a sodium ion battery.

8. A negative electrode material for a sodium ion battery, comprising a negative electrode active material and a binder, characterized in that: The negative electrode active material is the negative electrode active material according to claim 6.

9. A sodium ion battery negative electrode, characterized in that: The negative electrode comprises a current collector and a negative electrode material coated and / or filled on the current collector, and the negative electrode material is the negative electrode material according to claim 8.

10. Use of the sodium ion battery negative electrode according to claim 9 in a sodium ion battery; Preferably, the sodium ion battery comprises an electrode group and a non-aqueous electrolyte, wherein the electrode group and the non-aqueous electrolyte are sealed in a battery housing, and the electrode group comprises a positive electrode, a negative electrode and a separator, wherein the separator is located between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Carbon / carbon composite microsphere material, production method and lithium ion battery

    CN103214245A

  • Pyrolysis amorphous carbon material and preparation method and application thereof

    CN105098186A

  • Performance improvement method and application of sodium-ion battery carbon-based negative electrode material

    CN113526489A

  • Porous hard carbon negative electrode material based on asphalt as well as preparation method and application of porous hard carbon negative electrode material

    CN115676804A

  • Sodium-ion battery core-shell structure bagasse hard carbon-based negative electrode material and preparation method thereof

    CN116332152A